Gentle stroking elicits somatosensory ERP that differentiates between hairy and glabrous skin. Issue 9 (21st February 2022) - Schirmer, Annett; Lai, Oscar; McGlone, Francis; Cham, Clare; Lau, Darwin
Abstract: Here we asked whether, similar to visual and auditory event-related potentials (ERPs), somatosensory ERPs reflect affect. Participants were stroked on hairy or glabrous skin at five stroking velocities (0.5, 1, 3, 10 and 20 cm/s). For stroking of hairy skin, pleasantness ratings related to velocity in an inverted u-shaped manner. ERPs showed a negativity at 400 ms following touch onset over somatosensory cortex contra-lateral to the stimulation site. This negativity, referred to as sN400, was larger for intermediate than for faster and slower velocities and positively predicted pleasantness ratings. For stroking of glabrous skin, pleasantness showed again an inverted u-shaped relation with velocity and, additionally, increased linearly with faster stroking. The sN400 revealed no quadratic effect and instead was larger for faster velocities. Its amplitude failed to significantly predict pleasantness. In sum, as was reported for other senses, a touch's affective value modulates the somatosensory ERP. Notably, however, this ERP and associated subjective pleasantness dissociate between hairy and glabrous skin underscoring functional differences between the skin with which we typically receive touch and the skin with which we typically reach out to touch.